A cooperative game theoretic analysis of electric vehicles parking lot in smart grid. (15th October 2017) - Aghajani, Saemeh; Kalantar, Mohsen
Abstract: Plug-in Hybrid Electric Vehicles (PHEVs) play a major role in decreasing amount of fossil fuels led by transportation system. PHEVs in both Grid-to-Vehicle (G2V) and Vehicle-to-Grid (V2G) modes can effect on the power market. In order to diminish potential challenges related to these effects, various methods like developing optimal charging strategies for the connected PHEVs and managing energy exchange between the PHEVs' parking lots can be taken into consideration. In this paper, a cooperative game model has been proposed in order to determine charging/discharging price adaptively. Simulation results show how this model leads to the maximization of utilities' profit and minimization of the parking lots' cost. Furthermore, a stochastic analysis has been done over the proposed model in order to well understand how much the deviation of profit and expected value of profit are in different levels of uncertainty. The numerical results prove that higher deviation over spot market price leads to both higher mean and deviation over profit for utilities, and the owner of utilities should consider the effect of price's uncertainty whenever it is considerable. Highlights: Providing a cooperative game theory to model the interaction between utility and PL. Minimizing the operating cost of PLs, and maximizing the profit of utilities. Proposing a stochastic game model for utility which have interaction with main grid. Considering the degradation of PHEVs' batteries in operating cost functions.